The Positive Impact of E-LKPD Material on Number Patterns Based on Computational Thinking with the Malay Islamic Context on Students' Mathematical Reasoning - Angge Sapto Mubharokh; Hapizah; Ely Susanti (Jurnal Pendidikan dan Pengajaran, 2023)
Learners still need help in using patterns and relationships to analyze mathematical situations. This study aimed to positively impact E-LKPD on number pattern material based on computational thinking with Malay Islamic context on students' mathematical reasoning. This research is design research with the type of development studies that have preliminary research, prototype stage, and summative evaluation stages. Data collection techniques in this research are questionnaires, interviews, and tests. The data analysis techniques in this study are questionnaires and interviews conducted qualitatively and tests measured based on mathematical reasoning indicators. The result of this research is that the E-LKPD developed is valid, obtained from expert validation and confirmation of students who get comments and suggestions. In addition, the E-LKPD, which is practical, can be seen in students responding to the E-LKPD. Applying E-LKPD allows students to write what is known from the problem, find patterns, and connect them to determine the right solution procedure. The research conclusion shows that applying E-LKPD based on computational thinking impacts students' mathematical reasoning ability. The implication of this research can improve students' critical thinking skills.